Defective Autophagy in Atherosclerosis: To Die or to Senesce?. (26th February 2018) - Grootaert, Mandy O. J.; Roth, Lynn; Schrijvers, Dorien M.; De Meyer, Guido R. Y.; Martinet, Wim
Abstract : Autophagy is a subcellular process that plays an important role in the degradation of proteins and damaged organelles such as mitochondria (a process termed "mitophagy") via lysosomes. It is crucial for regulating protein and mitochondrial quality control and maintaining cellular homeostasis, whereas dysregulation of autophagy has been implicated in a wide range of diseases including atherosclerosis. Recent evidence has shown that the autophagic process becomes dysfunctional during the progression of atherosclerosis, regardless of whether there are many autophagy-stimulating factors (e.g., reactive oxygen species, oxidized lipids, and cytokines) present within the atherosclerotic plaque. This review highlights the recent insights into the causes and consequences of defective autophagy in atherosclerosis, with a special focus on the role of autophagy and mitophagy in plaque macrophages, vascular smooth muscle cells (VSMCs), and endothelial cells (ECs). It has been shown that defective autophagy can promote apoptosis in macrophages but that it accelerates premature senescence in VSMCs. In the ECs, defective autophagy promotes both apoptosis and senescence. We will discuss the discrepancy between these three cell types in their response to autophagy deficiency and underline the cell type-dependent role of autophagy, which may have important implications for the efficacy of autophagy-targeted treatments for atherosclerosis.